PEDAGOGICAL MODELING AND ITS TYPES - Kholliyeva Shakhlo Bakhtiyorovna (Zeta Repository, 2023)
The pedagogical models are different approaches to teaching that can be carried out by teachers in the classroom. Teachers perform a number of actions depending on the model they use and focus on different parts of the learning process. Because there are different ways to learn and each student is unique, teachers must be armed with different pedagogical models so that they can adapt to different situations.